Porous N-Doped Carbon-encapsulated Iron as Novel Catalyst Architecture for the Electrocatalytic Hydrogenation of Benzaldehyde - Colavita, Paula; Costa de Oliveira, Maida (My University, 2025)
Carbon porous materials containing nitrogen functionalities and encapsulated iron-based active sites have been suggested as electrocatalysts for energy conversion, however their applications to the hydrogenation of organic substrates via electrocatalytic hydrogenation (ECH) remain unexplored. Here- in, we report on a Fe@C:N material synthesized with an adapted annealing procedure and tested as electrocatalyst for the hydrogenation of benzaldehyde. Using different concentrations of the organic, and electrolysis coupled to gas chromatography experiments, we demonstrate that it is possible to use such architectures for the ECH of unsaturated organics. Potential control experiments show that ECH faradaic efficiencies > 70 % are possible in acid electrolytes, while maintaining selectivity for the alcohol over the pinacol dimerization product. Estimates of product formation rates and turnover frequency (TOF) values suggest that these carbon-encapsulated architectures can achieve competitive performance in acid electrolytes relative to both base and precious metal electrodes.
PUBLISHED
Keywords: Nanoscience & Materials